The Islamic rule for borrowing to perform worship acts. - كريمة معطالله، عمر مونة (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2023)
borrowing to perform acts of worship, and the opinions of the jurists varied in it between obligatory, admonition and prohibition, given that the origin of borrowing is permissibility and the permissible thing may be attracted by other mandated rulings according to the evidence and the conditions that adhere to it. Let us conclude that the least that can be said in the ruling on borrowing for worship is contrary to the first; Because in borrowing and debt there is hardship and a burden for the creditor with its misdeeds and incursions, and worship is built on the basis of hardship brings facilitation. The Sharia does not mean to charge people with what they cannot bear. Moreover, if the intention is to allow borrowing to perform acts of worship as a precaution for it and to absolve the one who is obligated from what is obligatory between him and God-the Mighty and Sublime - then the borrowing fills the dhimma with a debt and the right of others, and the rights of the servants are more firmly established. In contrast to the rights of God Almighty, which is based on forgiveness. Thus precaution in debt was more important than the one of performing worship